Glycosaminoglycans (GAGs) determination in healthy and damaged equine articular cartilage - Adarmes, Héctor; Donders, Leonardo; Dörner, Cristóbal; González, Ema; Galleguillos, Marco (Austral Journal of Veterinary Sciences, 2017)
The purpose of this study was to establish if there was any difference in the GAGs content between loaded and unloaded surfaces of the joint. Furthermore, the results were compared between macroscopically healthy and damaged joints. Cartilage samples were obtained from two different zones of the equine etacarpophalangeal joint (metacarpal condyles). Samples were collected from the loaded surface of macroscopically healthy joints (N1; n=10) and from macroscopically damaged cartilage (P1; n=10). Additionally, cartilage samples were collected from unloaded areas at the most dorso-proximal zone of the joint in macroscopically healthy joints (N2; n=10) and from the macroscopically pathological joints but without damaged cartilage on the site of sampling (P2; n=10). The GAGs were extracted from 100 mg of cartilage of each sample and quantified through the safranine - O method that measured the total anionic charges, and through the carbazole method that measured the uronic acid content. Both methods measured the GAGs content, showing no differences between intra-joint zones (1 and 2), but when the GAGs content was compared between healthy and pathological joints, both methods showed a significantly decreased GAGs content in the damaged joints (1 and 2). These results show that the whole articular cartilage could be affected in a chronic pathological process and is not only a local process occurring in the macroscopically damaged cartilage associated with the loaded area.